Scientific foundations of the movement of components of grain material with an artificially formed distribution of air velocity - С.П. Степаненко; Б.И. Котов; А.В. Спирин; В.Ю. Кучерук (Қарағанды университетінің хабаршысы. Физика сериясы)
The article examines the study of the separation of grain materials in pneumatic channels with an artificially generated distribution of air velocity in the cross-section channel to determine the rational form and parameters of the material supply and options for grain material separation into fractions. The regularities of the weevil movement were theoretically investigated and established in the form of mathematical models of the dynamics of the movement of a solid particle in airflow, which differ from the known ones by taking into account the action of lateral forces, the concentration of the material, and the use of a power-law and an artificially formed exponential law of air distribution facilitated to increase the differences (splitting) trajectories of caryopses by 20 %. The solution of the system of nonlinear differential equations with initial conditions is performed in the Mathcad software environment in the form of trajectories of the grain in the air flow. It allows calculating their trajectories, which differ in windage coefficients and determine the rational values of the parameters of pneumo-gravity and pneumo-inertia separators. Using the obtained dependencies for the development of air separators contributes to determine the initial speed of entry and the direction of entry of the kernels into the airflow, as well as to determine the trajectories of material movement in the air channels with the bottom unloading of material.